Book Review: Community Radio Policies in South Asia by Preeti Raghunath - Padmaja Shaw (tripleC: Communication, Capitalism & Critique)
Padmaja Shaw reviews “Community Radio Policies in South Asia” by Preeti Raghunath. Raghunath applies “deliberative policy ecology approach” to study how policy frameworks evolved in four South Asian nations, India, Bangladesh, Nepal and Sri Lanka. Raghunath argues that the “deliberative policy ecology approach” is rooted in emancipatory politics that brings in the stakeholders at the bottom of the policy food chain. Raghunath’s intricate map of policy formulation in post-colonial societies is an engaging revelation of the continued contradictions between the developmentalist instincts of the state and the push of grassroots voices to claim their legitimate space in decision making.